Dynamic doping and interphase stabilization for cobalt-free and high-voltage Lithium metal batteries - Ziqing Yao; Tianji Fu; Tao Pan; Chongyang Luo; Man Pang; Shizhao Xiong; Qingpeng Guo; Yujie Li; Shuangke Liu; Chunman Zheng; Weiwei Sun (Nature Communications)
Abstract Cobalt-free spinel LiNi0.5Mn1.5O4 (LNMO) positive electrodes, promise high energy density when coupled with lithium negative electrodes, due to the high discharge voltage platform. However, the intrinsic dissolution of Mn in positive electrode, electrolyte decomposition at high voltage, and dendrite growth on lithium severely compromise cycling stability, limiting the practical application. Herein, we propose ferrocene hexafluorophosphate as an electrolyte additive to achieve dynamic doping of Fe3+ in positive electrodes during electrochemical cycling. Furthermore, additive molecule preferentially decomposes at both the positive and negative electrode interfaces, forming thin, dense inorganic positive electrode electrolyte interphase and F, P-rich inorganic solid electrolyte interphase respectively, effectively stabilizing electrode interfaces. Consequently, the Li | |LNMO batteries based on modified electrolytes effectively enhance cycling stability and rate performance at a charge cutoff voltage of 4.9 V and an LNMO pouch cell performs consistently over 160 cycles. Additionally, the efficacy of ferrocene hexafluorophosphate extends beyond LNMO, demonstrating its universal applicability in stabilizing positive electrodes operating at challenging voltages, including LiNi0.8Co0.1Mn0.1O2, LiNi0.6Co0.2Mn0.2O2, and LiCoO2 and a 470 Wh kg−1 level Li metal pouch cell was successfully realized.